Volume 1: Symposia, Parts a and B 2012
DOI: 10.1115/fedsm2012-72491
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Reducing Vehicle Aerodynamic Drag

Abstract: A small scale model (length 1710 mm) of General Motor SUV was built and tested in the wind tunnel for expected wind conditions and road clearance. Two passive devices, rear screen which is plate behind the car and rear fairing where the end of the car is aerodynamically extended, were incorporated in the model and tested in the wind tunnel for different wind conditions. The conclusion is that rear screen could reduce drag up to 6.5% and rear fairing can reduce the drag by 26%. There were additional tests for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…Similar results were also presented by Pujals et al 27 with up to 10% reduction in drag, and Wood 5 with fuel economy improvement of 1%–5%. Other studies, however, noted either only marginal drag benefits (1.2%–1.7%) 28,29 or overall increases in drag. 28,30 The research suggests that while the supplementary vorticity results in increases in base pressure, the additional induced drag may outweigh the benefits.…”
Section: Introductionmentioning
confidence: 92%
“…Similar results were also presented by Pujals et al 27 with up to 10% reduction in drag, and Wood 5 with fuel economy improvement of 1%–5%. Other studies, however, noted either only marginal drag benefits (1.2%–1.7%) 28,29 or overall increases in drag. 28,30 The research suggests that while the supplementary vorticity results in increases in base pressure, the additional induced drag may outweigh the benefits.…”
Section: Introductionmentioning
confidence: 92%
“…Untuk mengatasi gaya hambat maka diperlukan desain bentuk kendaraan yang streamline demikian juga komponen-komponen aerodinamikanya. Salah satu komponen aerodinamika adalah wing sebagai passive option untuk reduksi drag [8]. Wing digunakan untuk memberikan gaya tekan ke bawah (downforce) atau gaya lift negatif.…”
Section: Pendahuluanunclassified
“…Sirenko et al [4] had shown higher fuel savings using rear screens and rear fairings for a light-duty General Motors SUV. Song et al [5] performed aerodynamic optimization of a sedan for drag reduction using artificial neural networks and CFD approach.…”
Section: Introductionmentioning
confidence: 99%